2015
DOI: 10.1109/tamd.2015.2426192
|View full text |Cite
|
Sign up to set email alerts
|

Staged Development of Robot Skills: Behavior Formation, Affordance Learning and Imitation with Motionese

Abstract: Inspired by infant development, we propose a three staged developmental framework for an anthropomorphic robot manipulator. In the first stage, the robot is initialized with a basic reach-and-enclose-on-contact movement capability, and discovers a set of behavior primitives by exploring its movement parameter space. In the next stage, the robot exercises the discovered behaviors on different objects, and learns the caused effects; effectively building a library of affordances and associated predictors. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 88 publications
0
39
0
Order By: Relevance
“…It becomes then relevant to understand in depth how the different processes involved in tutoring and learning interact. Drawing inspiration from the current human developmental study, we propose that future robots should start their learning by anticipating tutors' goal through action observation (Butz et al, 2003;Theofilis et al, 2013;Ugur et al, 2015). However this process should be overridable by any linguistic signal simultaneously provided by the tutor, averting robot's attention from the action target and potentially directing it toward how a goal is achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It becomes then relevant to understand in depth how the different processes involved in tutoring and learning interact. Drawing inspiration from the current human developmental study, we propose that future robots should start their learning by anticipating tutors' goal through action observation (Butz et al, 2003;Theofilis et al, 2013;Ugur et al, 2015). However this process should be overridable by any linguistic signal simultaneously provided by the tutor, averting robot's attention from the action target and potentially directing it toward how a goal is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Any source of information, be it the observation of their parents' actions or their verbal instruction, are exploited to rapidly acquire new action and linguistic competencies. Enabling robots to learn to understand human actions as human infants do is a promising research line pursued in current robotics research (e.g., Rohlfing et al, 2006;Cangelosi et al, 2010;Ugur et al, 2015). However, it is not yet clear how infants integrate efficiently the multimodal tutoring inputs provided simultaneously by their parents, in order to understand their actions.…”
mentioning
confidence: 99%
“…Previously we showed that a robot that is initialized with a basic reach-and-grasp movement capability can discover a set of action primitives, learn a library of affordances and associated predictors, and finally use these structures to bootstrap complex imitation with the help of a cooperative tutor [10]. The methods provided in the current study enable the robot to reach a higher level of cognitive competence, where it forms structures for planning at a symbolic level.…”
Section: Introductionmentioning
confidence: 91%
“…The approach was based on a cycle of exploration-manipulation, initialized with a collection of minimal knowledge and innate capabilities. These works studied the discovery of meaningful discrete motion primitives [10] or sequences thereof [8], using stochastic and deterministic [16] approaches. This allowed a robot to learn object affordances and the predictors that anticipate the effects that these action primitives create.…”
Section: Related Work On Object Affordance Discoverymentioning
confidence: 99%